Multiple-Drugs-Related Osteonecrosis of the Jaw in a Patient Affected by Multiple Myeloma: A Case Report - Mario Caggiano; Federica Di Spirito; Alfonso Acerra; Marzio Galdi; Laura Sisalli (MDPI AG, 2023)
A 60-year-old woman suffering from multiple myeloma (MM) was treated with zoledronic acid (bisphosphonate), dexamethasone (corticosteroid), bortezomib (a chemotherapeutic agent), and lenalidomide (thalidomide analog) for about a year and with lenalidomide alone as maintenance therapy for almost two years and developed stage three medication-related osteonecrosis of the jaws (MRONJ) in the upper left dental arch approximately two weeks after tooth extraction, which was treated with a medical nonoperative conservative approach until reversion to stage one. The present case report describing the development of multi-drug-related osteonecrosis of the jaws during the pharmacologic MM maintenance phase draws attention to the complex multidisciplinary and multistage management of MM subjects and also that during disease remission, crucially involving oral healthcare providers for MRONJ prevention and pharmacovigilance. To prevent similar cases, cancer patient management should ensure proper dental care not only before starting but also throughout therapy duration and ensure continuous interdisciplinary consensus between oncologists and dentists. Moreover, also considering the independent negative and potentially synergistic effect on bone metabolism and mucosal healing processes of employed medicaments, additionally combined with the cumulative one of previous intravenous bisphosphonates, further studies should highlight the polypharmacy effect and hopefully aid in patient-specific MRONJ risk assessment in cancer patients.